Flourishing and academic engagement among adolescents with overweight and obesity - Rupp, Kristie; McCoy, Stephanie M. (International Journal of Adolescent Medicine and Health, 2018)
Abstract Background Overweight and obesity in adolescence are associated with several negative health indicators; the association with flourishing, an indicator of overall well-being, is less clear. Objectives To examine associations between weight status and indicators of flourishing and academic engagement in adolescents. Subjects Analyses included 22,078 adolescents (10–17 years) from the 2016 National Survey of Children’s Health. Methods Adolescents were grouped according to body mass index (BMI) classification; outcomes included indicators of flourishing and academic engagement. Logistic regression models assessed the odds of each outcome comparing adolescents with overweight and adolescents with obesity to healthy weight adolescents. Results For flourishing, adolescents with overweight and adolescents with obesity were less likely to stay calm during a challenge (17% and 30%, respectively; p < 0.01); adolescents with obesity were 30% less likely to finish a task they started (p < 0.001), and 34% less likely to show interest in new things (p < 0.001) in comparison to healthy weight peers. Adolescents with obesity were 26% less likely to care about doing well in school (p < 0.001), and adolescents with overweight and adolescents with obesity were significantly less likely to complete all required homework (19% and 34%, respectively) (p < 0.001), in comparison to healthy weight peers. Conclusions A comprehensive approach to addressing overweight and obesity in adolescence should target improving academic engagement and flourishing to promote overall well-being.
Keywords: academics; adolescence; dept.hms; dept.pch; flourishing; obesity; peer-reviewed

Bullying perpetration and victimization among adolescents with overweight and obesity in a nationally representative sample - Rupp, Kristie; McCoy, Stephanie M. (Childhood Obesity, 2019)
Keywords: dept.hms; peer-reviewed

Physical Activity And Bullying In Adolescents With Overweight And Obesity - McCoy, Stephanie M.; Rupp, Kristie (Medicine and Science in Sports and Exercise, 2020)
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Understanding health behaviors, weight perceptions, and body appreciation of young adult women engaged in the body positivity movement - Rupp, Kristie; McCoy, Stephanie M. (Women's Health Issues, 2023)
Background The body positivity movement on social media is thought to foster body appreciation, but pervasive societal concern persists about the body positivity movement and the body image, health behaviors, and “normalization of obesity” of young adult women. Purpose This study explored the relationship between engagement in the body positivity movement on social media and weight status, body appreciation, body dissatisfaction, and the health behaviors of intuitive eating and physical activity in young adult women (18–35 years). Methods Participants (N = 521; ∼64% engaged in body positivity content on social media) were recruited using Qualtrics online panels for this cross-sectional survey during February 2021. Outcomes included weight status, weight consideration, weight perception, body appreciation, body dissatisfaction, physical activity, and intuitive eating. Logistic and linear regression models adjusted for age, race, ethnicity, education level, and household income were used to assess the association between engagement in the body positivity movement and specified outcomes. Results Engagement in body positivity content was associated with greater body dissatisfaction (β = 2.33, t(519) = 2.90 p = .017), body appreciation (β = 0.26, t(519) = 2.90 p = .004), and greater likelihood of reporting high amounts of physical activity (odds ratio = 2.28; p < .05) relative to nonengaged peers; these associations remained significant after further adjustment for weight status. Body positivity was not associated with weight status, weight perception, or intuitive eating. Conclusions Engagement in the body positivity movement is associated with higher body dissatisfaction and body appreciation in young adult women, which suggests they may be drawn to and engage in the body positivity movement as a protective or coping mechanism for body dissatisfaction.
Keywords: dept.hms; peer-reviewed